Relationship Between Risk Factors and Brain Reserve in Late Middle Age: Implications for Cognitive Aging - Neth, Bryan J.; Graff-Radford, Jonathan; Mielke, Michelle M.; Przybelski, Scott A.; Lesnick, Timothy G.; Schwarz, Christopher G.; Reid, Robert I.; Senjem, Matthew L.; Lowe, Val J.; Machulda, Mary M.; Petersen, Ronald C.; Jr., Clifford R. Jack; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Brain reserve can be defined as the individual variation in the brain structural characteristics that later in life are likely to modulate cognitive performance. Late midlife represents a point in aging where some structural brain imaging changes have become manifest but the effects of cognitive aging are minimal, and thus may represent an ideal opportunity to determine the relationship between risk factors and brain imaging biomarkers of reserve. Objective: We aimed to assess neuroimaging measures from multiple modalities to broaden our understanding of brain reserve, and the late midlife risk factors that may make the brain vulnerable to age related cognitive disorders. Methods: We examined multimodal (structural and diffusion MRI, FDG PET) neuroimaging measures in 50-65 year olds to examine the associations between risk factors (Intellectual/Physical Activity: education-occupation composite, physical and cognitive-based activity engagement; General Health Factors: presence of cardiovascular and metabolic conditions, body mass index, hemoglobin A1c, smoking status (ever/never), CAGE Alcohol Questionnaire (>2, yes/no), Beck Depression Inventory score), brain reserve measures (Dynamic: genu corpus callosum fractional anisotropy, posterior cingulate cortex FDG uptake, superior parietal cortex thickness, AD signature cortical thickness; Static: intracranial volume), and cognition (global, memory, attention, language, visuospatial) from a population-based sample. We quantified dynamic proxies of brain reserve (cortical thickness, glucose metabolism, microstructural integrity) and investigated various protective/risk factors. Results: Education-occupation was associated with cognition and total intracranial volume (static measure of brain reserve), but was not associated with any of the dynamic neuroimaging biomarkers. In contrast, many general health factors were associated with the dynamic neuroimaging proxies of brain reserve, while most were not associated with cognition in this late middle aged group. Conclusion: Brain reserve, as exemplified by the four dynamic neuroimaging features studied here, is itself at least partly influenced by general health status in midlife, but may be largely independent of education and occupation.